2019
DOI: 10.3389/fmars.2019.00528
|View full text |Cite
|
Sign up to set email alerts
|

Net Community Production and Carbon Exchange From Winter to Summer in the Atlantic Water Inflow to the Arctic Ocean

Abstract: The eastern Fram Strait and area north of Svalbard, are influenced by the inflow of warm Atlantic water, which is high in nutrients and CO 2 , influencing the carbon flux into the Arctic Ocean. However, these estimates are mainly based on summer data and there is still doubt on the size of the net ocean Arctic CO 2 sink. We use data on carbonate chemistry and nutrients from three cruises in 2014 in the CarbonBridge project (January, May, and August) and one in Fram Strait (August). We describe the seasonal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 81 publications
(121 reference statements)
4
17
1
Order By: Relevance
“…Concentrations of PO 4 were also high, reaching 1.7 µmol L −1 in river samples in August. These concentrations are higher than concentrations measured from AW advected from the shelf (maximum of 2 µmol L −1 for NO 2 + NO 3 and 0.4 µmol L −1 for PO 4 in this study, but other observations from Svalbard show 6-11 µmol L −1 for N and 0.8 µmol L −1 for P (Chierici et al, 2019;Halbach et al, 2019). While SiO 2 has been associated with glacial meltwater from contact with silica-rich bedrock in Isfjorden (Fransson et al, 2015), Kongsfjorden (Halbach et al, 2019) and Greenland fjords (Meire et al, 2016;Kanna et al, 2018;Hendry et al, 2019), N and P have been linked primarily to advected deep water.…”
Section: River Water Chemistry Changes Seasonallycontrasting
confidence: 87%
“…Concentrations of PO 4 were also high, reaching 1.7 µmol L −1 in river samples in August. These concentrations are higher than concentrations measured from AW advected from the shelf (maximum of 2 µmol L −1 for NO 2 + NO 3 and 0.4 µmol L −1 for PO 4 in this study, but other observations from Svalbard show 6-11 µmol L −1 for N and 0.8 µmol L −1 for P (Chierici et al, 2019;Halbach et al, 2019). While SiO 2 has been associated with glacial meltwater from contact with silica-rich bedrock in Isfjorden (Fransson et al, 2015), Kongsfjorden (Halbach et al, 2019) and Greenland fjords (Meire et al, 2016;Kanna et al, 2018;Hendry et al, 2019), N and P have been linked primarily to advected deep water.…”
Section: River Water Chemistry Changes Seasonallycontrasting
confidence: 87%
“…These values are much higher than our maximum NCP rate in eastern Baffin Bay of 5.7 mol C m -2 ; however, given the declining NCP and primary production trends over the past decade within the North Water region (Bélanger et al, 2013;Bergeron and Tremblay, 2014;Blais et al, 2017;, such high rates of NCP are no longer occurring within that region. Our reported seasonal NCP rates within the Atlantic sector of Baffin Bay (1.4-5.7 mol C m -2 ) fall in the same approximate range as those reported more recently in the productive Barents Sea (2.3-4.2 mol C m -2 ; Fransson et al, 2001;Codispoti et al, 2013;Chierici et al, 2019).…”
Section: Comparison With Previous Studiessupporting
confidence: 89%
“…The mean atmospheric CO 2 uptake of 0.86 ± 0.63 mmol m −2 day −1 is similar to that of 0.73 ± 0.40 mmol m −2 day −1 estimated for a marginal Arctic coastal environment of Hudson Bay, Canada (Else et al, 2008b). Wind speeds in Kaldfjorden were dampened due to orographic steering, compared to measurements off the shelf (Nordby et al, 1999); thus, atmospheric CO 2 uptake in Kaldfjorden of 2.7 mmol m -2 day -1 is weak compared with the CO 2 influx of >15 mmol m −2 day −1 for the Norwegian Sea (Yasunaka et al, 2016) and the nonice-covered Arctic shelf seas that generally absorb CO 2 at between 1 and 15 mmol m −2 day −1 (Omar et al, 2005;Cai et al, 2006;Else et al, 2008aElse et al, , 2013Ericson et al, 2018;Chierici et al, 2019). Enhanced CO 2 uptake in higher latitude waters results from substantial blooms, greater biological productivity and subsequent export of organic matter to deeper waters, coupled to strong winds enhancing oceanic CO 2 uptake.…”
Section: Ocean Acidification State and Co 2 Uptakementioning
confidence: 94%
“…Calcium carbonate (CaCO 3 ) saturation state (Ω) for the biomineral aragonite and the surface water fugacity of CO 2 (fCO 2 ) were determined from C T and A T , and in situ temperature, salinity, pressure and macronutrient concentrations using the CO 2 system program CO2SYS (Lewis and Wallace, 1998;van Heuven, 2011). The carbonic acid dissociation constants (pK 1 and pK 2 ) of Mehrbach et al (1973) as refit by Dickson and Millero (1987) were selected, as they have shown good agreement between measured and calculated values in Arctic waters (Chen et al, 2015;Woosley et al, 2017) and were selected for similar studies in sub-Arctic/Arctic regions (Chierici et al, 2019;Ericson et al, 2019). Ω is used as an indicator for changes in carbonate chemistry in relation to ocean acidification.…”
Section: Hydrographic Measurementsmentioning
confidence: 99%